2021
DOI: 10.1177/00031348211030464
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lumpectomy and Cavity Shave Margin Status on Recurrence and Survival in Breast-Conserving Surgery

Abstract: Background/Objective Cavity shave margins (CSMs) decrease rate of positive margins and need for re-excision. Recurrence data following breast-conserving surgery (BCS) are not always available in large cancer registries. We sought to define our recurrence and survival data in BCS with routine excision of CSMs. Methods A single institution, 10-year retrospective review of breast cancer patients who underwent BCS with routine CSMs was conducted. Cavity shave margin technique was standard. Cox proportional hazard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Comparing the incidence of positive margins in our study with the current literature, we observed a significant reduction in the number of margins infiltrated by the neoplasia [15,16]. Based on those findings, either the cavity shave technique or the intraoperative histopathological examination of the specimen is necessary in order to reduce the rate of reintervention.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Comparing the incidence of positive margins in our study with the current literature, we observed a significant reduction in the number of margins infiltrated by the neoplasia [15,16]. Based on those findings, either the cavity shave technique or the intraoperative histopathological examination of the specimen is necessary in order to reduce the rate of reintervention.…”
Section: Discussionsupporting
confidence: 72%
“…Kobbermann et al, in a retrospective study found that before the introduction of the cavity shaving technique, re-operation for positive margins was 42% and reduced to 22% with the introduction of the cavity shave [15]. Marudanayagam et al found that routine cavity shaving was associated with a lower rate of positive margins (6% vs. 12%) [16].…”
Section: Discussionmentioning
confidence: 99%